2019
DOI: 10.1590/1677-5449.180062
|View full text |Cite
|
Sign up to set email alerts
|

Superior vena cava syndrome: endovascular management

Abstract: BackgroundThe objective of management of superior vena cava syndrome (SVCS) is to promptly alleviate the uncomfortable symptoms. Conventional approaches do not always achieve results as rapidly as endovascular management with stent placement.ObjectivesTo report the experience with endovascular management of SVCS of a Vascular and Endovascular Surgery Service at a Brazilian university hospital.MethodsSymptomatic type III SVCS cases were managed with angioplasty and stent placement in 28 patients aged from 37 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our patient's survival time was 7 months. that is in line with endovascular management of SVCS of Vascular and Endovascular Surgery Service of Brazilian University hospital where they managed 28 patients between 2002 and 2012 (11).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our patient's survival time was 7 months. that is in line with endovascular management of SVCS of Vascular and Endovascular Surgery Service of Brazilian University hospital where they managed 28 patients between 2002 and 2012 (11).…”
Section: Discussionsupporting
confidence: 62%
“…This type of recanalization provides immediate symptomatic relief of vein thrombosis in patients with a terminal stadium of the disease (6,7,10,11). At the terminal stage the survival time ranges from 3 to 6 months (10,11). Our patient's survival time was 7 months.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Despite its poor efficacy, stent placement, which had the advantage of quickly relieving symptoms, is currently considered to be the first-line treatment (6). It was reported that 90% of patients who underwent stent placement show evident clinical improvement in 24 to 48 hours (7). However, stent placement also has complications such as stent displacement, obstruction, and pericardial tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…Superior vena cava syndrome (SVCS) is a generic term for a syndrome in which compression or obstruction of the SVC impairs the return of venous blood to the heart and causes venous depression in the head, neck, chest, and upper limbs [2]. In the etiology of SVCS, most cases (85%) occur in the presence of malignant disease, particularly bronchogenic carcinomas, lymphomas and metastatic tumors [3]. We experienced a case of SVCS due to mediastinum lymph node metastasis and report the clinical findings, images, cytology, treatment, progress and various considerations.…”
Section: Introductionmentioning
confidence: 99%